Indonesia, Malaysia, China Stock Market Long-Term Analysis - Amsal Irmalis; Fajri Hadi; Mirdha Fahlevi SI (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2020)
The present paper examines the long-run relationship between the Indonesia Stock Exchange (IDX), Malaysia Stock Exchange (Bursa Malaysia) and China Stock Market (SSE). The data used is the daily price index (daily price) of the composite shares (Composite Index) of each country from 2012-2018. The method used is the bivariate and multivariate cointegration approach with testing using the Johansen Test. To strengthen the proof of independence or interdependence of the capital markets of these countries, an Impulse Responses Function and Var Decomposition test will be conducted.